Disaster Tourism Destinations: Exploring the Motivations and Intentions of Tourist Visits : Case Study on Lava Tour of Mount Merapi Yogyakarta - Widianto, Tri; Yulia, Yosephine Angelina (Jurnal E-Bis, 2023)
Lava Tour is a visitor tour with a trip to a location related to the volcanic eruption in Sleman Yogyakarta. The aim of this research is to identify the phenomenon of disaster tourism on the Mount Merapi Lava Tour in Yogyakarta. This research collected data from 127 tourists on the Merapi Lava Tour. To determine the relationship between push motivation variables (emotional fulfillment, tourism information, and search for truth) and pull motivation variables (historical heritage, convenient location, and knowledge of tourist attractions) on satisfaction variables and intention to revisit variables, PLS-SEM was used. According to research findings, the positive relationship between satisfaction and intention to return has a dominant influence, based on the coefficient value of each predictor. This suggests that the main motivations for returning are emotional fulfillment, truth seeking, a comfortable atmosphere, and knowledge of tourist attractions, all of which make visitors feel satisfied.